PERANCANGAN ANTARMUKA APLIKASI ANDROID PENGENALAN EMOSI SUARA MANUSIA PADA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN MAJALENGKA - Rahmatunnisa, Elsa Nabila; Prasetyo , Tri Ferga (Universitas Majalengka, 2025)
The development of artificial intelligence technology has opened up opportunities for the application of Speech Emotion Recognition (SER) in various fields, including arts and culture. Manual voice emotion assessment is often subjective, so a more objective and practical application-based solution is needed. This study aims to design an Android application interface to recognize various human voice emotions that can support the Tourism and Culture Office at Majalengka Regency (Disparbud Majalengka) in evaluating artistic and cultural expressions. The methodology used is Rapid Application Development (RAD), which emphasizes the speed of iteration and prototyping by involving user feedback. The research process included literature studies, observations, interviews, needs analysis, wireframe design, UML diagram creation, and interface implementation using Android Studio with the Kotlin programming language. The implementation results showed that the application was able to provide key features such as voice recording, emotion analysis, recording history storage, and data management. Testing was conducted using Black Box Testing to ensure that the system functions according to specifications, as well as the System Usability Scale (SUS) method to assess the user experience. The SUS score obtained shows that the application is in the “acceptable” category and is therefore suitable for use. This research is expected to support technological innovation in the development of local arts and culture.